Pressure injuries in Australian public hospitals: A cost of illness study. (June 2022) - Nghiem, Son; Campbell, Jill; Walker, Rachel M; Byrnes, Josh; Chaboyer, Wendy
Abstract: Background: Pressure injuries are a leading hospital adverse event, yet they are mostly preventable. Understanding their financial costs will help to appreciate the burden they place on the health system and assist in better planning and management of health expenditures to prevent pressure injuries. Objective: To estimate the cost of pressure injuries in Australian public hospitals in 2020 demonstrating its economic burden in a well–resourced health system. Methods: A cost of illness study with a 12-month time horizon was conducted. Resource use for the treatment of pressure injuries and productivity loss due to pressure injuries were derived using a bottom-up approach. Parameters of the cost estimates were obtained from secondary sources and literature syntheses. A simulation with 10, 000 draws was used to generate statistical properties of the cost estimates. Results: Based on a prevalence of 12.9%, the total cost of pressure injuries in Australian public hospitals was 9.11 billion [95% confidence intervals: 9.02, 9.21]. The two largest shares of costs were accounted for by the opportunity cost of excess length of stay of 3.60 billion [3.52, 3.68] and treatment costs of 3.59 billion [3.57, 3.60]. Productivity loss associated with pressure injuries amounts to 493 million [482, 504]. Hospital-acquired pressure injuries account for a total of 5.50 billion [5.44, 5.56], whereas pressure injuries present on admissions costed 3.71 billion [3.70, 3.72]. In terms of severity, Stage 2 pressure injuries contributed the most to total treatment costs, total excessive length of stay, and total loss of healthy life years. Australian society is willing to pay 1.43 billion [1.40, 1.45] to save 6, 701 [6, 595; 6, 807] healthy life years lost by pressure injury. Conclusions: Reducing preventable pressure injuries and stopping the progression of Stage 1 pressure injuries will likely result in an immense cost-saving for Australia and will likely have similar benefits for other countries with comparable profiles. Tweetable abstract : Australian public hospital study provides comprehensive analysis of the cost of pressure injury, including estimates of direct and indirect medical costs, and indirect non-medical costs - such as productivity and quality of life.